PEMBENTUKAN VERBA NANA- -(K) DALAM BAHASA ROTE: ANTARA PASIF DAN ANTIKAUSATIF - Balukh, Jermy Imanuel (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2008)
Abstract This paper discloses the overlapping relationship between passive and anticausative in Rotenese. Passive and anticausative have similarity in concept; the syntactic valence decreasing from transitive to intransitive form. However, the two constructions have differences; the agent of passive construction is optional, while the agent of anticausative construction is never expressed. The analysis on Rotenese data shows that the marker nana- -(k) occurs when object is promoted to subject. In this case, the subject is demoted from the construction and even omitted. This indicates that the construction tends to be anticausative. Such construction can be also claimed as agentless passive because of the explicit formal marking.